Math, asked by dhayalvinod3, 8 months ago

5. Show that.
(1) (3x + 7)2 - 84x = (3x - 7)2​

Answers

Answered by ajayjms7
5

L.H.S = (3x + 7)2 − 84x = (3x)2 + 2(3x)(7) + (7)2 − 84x = 9x2 + 42x + 49 − 84x = 9x2 − 42x + 49 R.H.S = (3x − 7)2 = (3x)2 − 2(3x)(7) +(7)2 = 9x2 − 42x + 49 L.H.S = R.H.S

Answered by pranitagajele
0

Answer:

LHS =(3x+7)

2

−84x

Using , (a+b)

2

=a

2

+2ab+b

2

=(9x

2

+42x+49)−84x

=9x

2

−42x+49

Using , (a−b)

2

=a

2

−2ab+b

2

=(3x)

2

−2(3x)(7)+(7)

2

=(3x−7)

2

= RHS

Similar questions